Survival and Cost-Effectiveness of Trabectedin Compared to Ifosfamide Monotherapy in Advanced Soft Tissue Sarcoma Patients - Verboom, Michiel C. (Sarcoma, 2019)
Trabectedin and ifosfamide are among the few cytostatic agents active in advanced soft tissue sarcomas (STSs). Trabectedin is most potent against so-called L-sarcomas (leiomyosarcoma and liposarcoma). The survival gain and cost-effectiveness of these agents in a second-line setting were analysed in the setting of advanced STS after failure of anthracyclines. A prospective observational trial had previously been performed to assess the use of trabectedin in a Dutch real-world setting. Data on ifosfamide monotherapy were acquired from previous studies, and an indirect comparison of survival was made. A state-transition economic model was constructed, in which patients could be in mutually exclusive states of being preprogression, postprogression, or deceased. The costs and quality-adjusted life years (QALYs) for both treatments were assessed from a Dutch health-care perspective. Separate analyses for the group of L-sarcomas and non-L-sarcomas were performed. Trabectedin treatment resulted in a median progression-free survival of 5.2 months for L-sarcoma patients, 2.0 months for non-L-sarcoma patients, and a median overall survival of 11.8 and 6.0 months, respectively. For L-sarcoma patients, trabectedin offered an increase of 0.368 life years and 0.251 QALYs compared to ifosfamide and €20,082 in additional costs, for an incremental cost-effectiveness ratio (ICER) of €80,000 per QALY gained. In the non-L-sarcoma patients, trabectedin resulted in 0.413 less life years and 0.266 less QALYs, at the increased cost of €4,698. The difference in survival between drugs and the acquisition costs of trabectedin were the main influences in these models. Trabectedin was shown to have antitumour efficacy in advanced L-sarcoma. From a health economics perspective, the costs per QALY gained compared to ifosfamide monotherapy that may be acceptable, considering what is currently regarded as acceptable in the Netherlands.